Requirements Effectiveness to Obtain License C (SIM) in Pressing of Traffic Accidents - Sarpan Sarpan; Sri Kusriyah (Law Development Journal, 2020)
This study aims to determine and analyze the effectiveness of reducing traffic accidents in Purworejo by encouraging children aged 17 years to have a license C, and to reduce traffic accidents seen from Article 81 paragraph (2) letter A of Act No. 2 Of 2009. Methods approach used in this study is a sociological juridical approach. The research specification is descriptive analytical. In this research, the analysis used is qualitative analysis. The results of this study are: 1) The effectiveness of the 17 year age setting as a condition of obtaining a Class C Driving License (SIM C) in order to reduce traffic accidents in Purworejo has been effective, because teenagers who have a license C can better understand the procedures for driving a motorized vehicle on the highway and obey more traffic rules. According to the examiner, the age limit of 17 years to obtain a license C is not suitable in order to reduce traffic accidents. There is no need to change the age limit of 17 years, only to be tightened in testing the license so that the quality of the license better reflects the driver's competence. 2) The role of the police in reducing traffic accidents, seen from Article 81 Paragraph 2 Letter A of Act No. 22 Of 2009, is sufficiently good in its implementation and ideal as well as the application of sanctions given to perpetrators of road accidents on a regular basis.